Influence of User-Generated Content on Promotion of Business - NavithaSulthana, A.; S.Vasantha, Dr. (International Journal of Engineering and Technology, 2018)
This paper examines how user-generated content promote the business through social media.The authorreviewed variousliteratures relatedto user-generated content on promotion of business. Based on the reviewsthe researcher developed a proposed conceptual model. The study examines the usefulness of user-generated content from various social media platform. It was found that user-generated contentfacilitatesbrand awareness, buildbrand trust and increase the sale.The advancement of web 2.0 technology which over come traditional one way communication into two way communication using social media. User-generated content (UGC) on social media create and share information among the other online user. In the current era user-generated content is the powerful content where user shares their experience actively in organic form. The term user-generated content indicates, thecontent is created and shared by the user. Consumer generated media or user-generated media created by user are shared, viewed among one user to another user of same interested community.
Keywords: Promotion of Business; Social Media Platforms and User-Generated Content